Strategi Dalam Meningkatkan Pelaku UKM Pasca COVID-19 - Edy Noor; Mahmudi Akhirin; Reni Widiawati; Muhamad Yudha Nugraha; Rahmad Batu Bara; Safrida Safrida; Supar Wasesa; Sri Rahayu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research is motivated by many compalints of small and medium business actors during the Covid-19 pandemic in many countries, including Indonesia, which occurred in early 2020 which was very influential on people’s purchasing power. In an effort to generate small and medium enterprises, various strategies are needed to gain market share so that buyers are interested so as to increase sales. Marketing activities must be carried out effectively and efficiently and focus on product quality, promotion, and sales. In this case, an active role and management strategy is needed from the Cooperative, Small and Medium Enterprises Kabupaten Batu Bara to increase sales of production results from small and medium bussiness actors after Covid-19. This research is focused on finding out the most effective strategy used to achieve maximum sales results. The research method used is qualitative research, with interviews with Head of Offices, small and medium business actors and business actors, and other data obtained from varios existing book references. From the results of the study indicate that the marketing strategy carried out is to choose the market, product, distribution and promotion. The most effective marketing strategy is promotion through social media and advertising.